2022
DOI: 10.1088/1755-1315/950/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals (Pb and Cd) contents in the seawater and sediment in Panjang and Pamujaan Besar Islands, Banten Bay, Indonesia

Abstract: The industrial activities in the coastal area of Banten Bay harmed water quality and tourism aesthetics. This study aims to determine the accumulation of heavy metals Pb and Cd in the water and sediment, which was conducted for 3 months from May until July in 2019 in Pulau Panjang and Pamujaan Besar. Data were collected by using the purposive sampling method. The water samples were studied using Van Dorn Water Sampler, while sediment samples were undertaken using Peterson Grab. The concentration of Pb and Cd i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Heavy metal is a hazardous contaminant that causes lethal and non-lethal effects in aquatic creatures, such as decreased growth, behavior, and morphological traits (Usero et al 2005). It can enter and accumulate in the body of aquatic organisms through the gills, body surface, digestive tract, muscles, and liver (Juniardi et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metal is a hazardous contaminant that causes lethal and non-lethal effects in aquatic creatures, such as decreased growth, behavior, and morphological traits (Usero et al 2005). It can enter and accumulate in the body of aquatic organisms through the gills, body surface, digestive tract, muscles, and liver (Juniardi et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…22 in 2021, which is 7-8.5. When compared with similar studies that measure the pH concentration of seawater, the research by Juniardi et al [20] has the same pH range, which ranges from 7.20 to 8.90.…”
Section: Discussionmentioning
confidence: 98%
“…Several research activities in Banten Bay were carried out, generally based on scientific fields and locations. Some of these research activities are the Physico-chemical conditions of Cengkok coastal waters [3], Bojonegara coastal waters [4], marine waters around Panjang Island and Pamujan Besar [5], plankton in Cengkok coastal waters [6], plankton at Bojonegara coastal waters [7], benthos in Cengkok coastal waters [8], heavy metal in several aquatic organisms [9][10][11][12][13][14], fish biology [15,16], and fish parasites [17]. However, study on zooplankton in this coastal waters has never been reported.…”
Section: Introductionmentioning
confidence: 99%